The Making of Good Work and Good People - Ramaswamy, Krithi D. (Graduate Institute Publications, 2025)
This ePaper critically examines community health schemes in India through the lens of one of the largest cadres of community health workers in the world, the Accredited Social Health Activists or ASHAs. Focusing on in-depth qualitative research with a group of ASHAs in New Delhi, India, this study aims to understand how work, labour, and volunteerism are understood in community health schemes. By mobilising sociological and anthropological literature on work, volunteerism and gendered frameworks of care, this research demonstrates how ideologies of altruistic service and morality are embedded in state narratives of social welfare and are used to undervalue the work of women from marginalised communities within public health care systems. At the same time, by centring the narratives of the ASHA workers themselves, this research also uncovers the complex social ties and narratives of community and care that the workers create to negotiate their precarious working conditions and advocate for their rights and their position within spaces of informalised formal work. We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master’s dissertations.